Rethinking ideology in the age of global discontent bridging divides - Axford, Barrie; Buhari-Gulmez, Didem; Gulmez, Seckin Baris (Routledge studies in Global and transnational politics, 2018)
Over the last decade, anti-government demonstrations worldwide have brought together individuals and groups that were often assumed unlikely to unite for a common cause due to differences in ideological tendencies. They have particularly highlighted the role of youth, women, social media, and football clubs in establishing unusual alliances between far left and far right groups and/or secular and religious segments of the society. In this wide-ranging volume, the contributors question to what extent political ideologies have lost their explanatory power in contemporary politics and society. This book aims to contribute to the ongoing debates about the relationship between ideology and public protests by introducing the global context that allows the comparison of societies in different parts of the world in order to reveal the general patterns underlying the global era. Tackling a highly topical issue, this book will be of particular interest to students and scholars of international relations, social movements and globalization."--Provided by publisher